2021
DOI: 10.1016/j.scitotenv.2020.142929
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of SARS-CoV-2 RNA in wastewater and treated effluents: Surveillance of COVID-19 epidemic in the United Arab Emirates

Abstract: Testing SARS-CoV-2 viral loads in wastewater has recently emerged as a method of tracking the prevalence of the virus and an early-warning tool for predicting outbreaks in the future. This study reports SARS-CoV-2 viral load in wastewater influents and treated effluents of 11 wastewater treatment plants (WWTPs), as well as untreated wastewater from 38 various locations, in the United Arab Emirates (UAE) in May and June 2020. Composite samples collected over twenty-four hours were thermally deactivated for safe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 28 publications
2
111
0
1
Order By: Relevance
“…For instance, in Australia, where comparatively lesser number of cases was reported, studies showed the presence of SARS-CoV-2 in 22% of the wastewater samples with the viral concentration being as low as 1.2 × 10 2 copies/L [25] . A similar study conducted in UAE reported the viral load in influents of 11 WWTPs and 38 other locations across the country [98] . Results showed that the viral load in wastewater from the WWTPs ranged between 7.5 × 10 2 to 3.4 × 10 4 copies/L.…”
Section: Sars-cov-2 In Wastewatermentioning
confidence: 85%
See 1 more Smart Citation
“…For instance, in Australia, where comparatively lesser number of cases was reported, studies showed the presence of SARS-CoV-2 in 22% of the wastewater samples with the viral concentration being as low as 1.2 × 10 2 copies/L [25] . A similar study conducted in UAE reported the viral load in influents of 11 WWTPs and 38 other locations across the country [98] . Results showed that the viral load in wastewater from the WWTPs ranged between 7.5 × 10 2 to 3.4 × 10 4 copies/L.…”
Section: Sars-cov-2 In Wastewatermentioning
confidence: 85%
“…The wastewater released from quarantine centers, hospitals, or households with COVID-19 patients is seen to play a potential role in the spread of infection. Recently, many attempts have been made to detect SARS-CoV-2 RNA in municipal wastewater samples from the countries like Australia, France, India, Israel, Italy, Japan, the Netherlands, Spain, Turkey, the USA, UAE, and many other countries around the globe [25] , [29] , [82] , [83] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] . The viral load of SARS-CoV-2 in feces of patients tested positive has been reported to be in the range of 10 4 -10 8 copies/L.…”
Section: Fate Of Sars-cov-2 In the Urban Water Cyclementioning
confidence: 99%
“…The current clinical disease surveillance, which does not adequately test asymptomatic individuals, limits the ability of decision makers to determine when and where outbreaks are occurring within their communities. Wastewater surveillance of SARS-CoV-2 is an emerging public health tool to understand the spread of COVID-19 in communities and is currently being implemented worldwide ( D'Aoust et al, 2021 ; Hasan et al, 2021 ; La Rosa et al, 2020 ; Medema et al, 2020 ; Peccia et al, 2020 ; Randazzo et al, 2020 ; Westhaus et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eleven sewage treatment plants in the United Arab Emirates surveyed in May and June 2020 had SARS-CoV-2 concentrations in their influent water ranging from 0.75 to 34 copies/mL. In addition, when the government took preventive measures, the confirmed cases of COVID-19 decreased significantly, and the SARS-CoV-2 concentration in wastewater samples exhibited a corresponding decrease ( Hasan et al, 2020 ). An April 2020 study in Germany found that all of the influent samples from nine sewage treatment plants were positive for SARS-CoV-2, with concentrations ranging from 2.6 to 37 copies/mL ( Westhaus et al, 2021 ).…”
Section: Wastewater and Covid-19mentioning
confidence: 99%